Utilização do heteropoliácido H3PW12O40 como catalisador em processos de valorização de compostos terpênicos - Kelly Alessandra da Silva Rocha (2008)
Heteropoly acids (HPAs), especially those of the Keggin series, are widely used as catalysts for the synthesis of fine and specialty chemicals. In this work the heteropoly acid H3PW12O40 (PW), the strongest HPA of the Keggin series, was applied as homogeneous (dissolved) and heterogeneous (silica-supported) catalyst in the reactions of isomerization, cyclization, and carbon-oxygen coupling of naturally occurring monoterpenes and their derivatives, which are low-prized row materials available in Brazil, in order to obtain more expensive commercially important products. Various products valuable for the fragrance industry have been obtained by the isomerization of a-pinene oxide using PW as an efficient and versatile catalyst. A good control of chemoselectivity has been achieved through the choice of the reactionconditions and solvent, whose polarity and basicity strongly affect the reaction pathways. Highly valuable campholenic aldehyde, trans-carveol, trans-sobrerol, and pinol can be obtained in 70-90% yield each using an appropriate solvent. Non-polar and non-basic solvents favor the formation of campholenic aldehyde. Polar basic solvents, favor the formation of trans-carveol; whereas in polar weakly basic solvents, such as acetone, nitrobenzene and acetonitrile, the major products obtained are trans-sobrerol and pinol. On the other hand, in a non-polar basic solvent, i.e., 1-4-dioxane, campholenic aldehyde and trans-carveol are formed in comparable amounts. The catalyst shows high turnover numbers (100 - 20 000), in this system. 1,8-Cineole and 1,4-cineole, both useful for flavoring and pharmaceutical applications, were synthesized by the isomerization of a-terpineol catalyzed by PW. In homogeneous system in nitrobenzene solutions, 1,8-cineole and 1,4-cineole were obtained with 25% and 23-27% selectivity, respectively, at 50-90% a-terpineol conversion. In the heterogeneous system, more satisfactory results were achieved: 1,8-cineol and 1,4 cineol were obtained with 35% and 25% selectivity, respectively, at 70-100% a-terpineol conversion using silica-supported PW as a solid acid catalyst in cyclohexane. The PW was also used a bifunctional catalyst together with Pd in the synthesis of (-)-menthol, which is the product of a great commercial interest employed in several segments of the chemical industry due to its characteristic odor and a physiological cooling effect produced. It was obtained by one-pot transformation of (+)-citronellal in a process in which the simultaneous cyclization and hydrogenation reactions occurred in a single step with the yield of 92% for the menthol at 100% citronellal conversion and85% stereoselectivity for the desired (-)-menthol. It has been also found that PW/SiO2 is an efficient, environmentally friendly heterogeneous catalyst for the synthesis of camphene and isolongifolene, both useful as intermediates in the synthesis of fragrances. They were synthesized by the isomerization of a-pinene and longifolene in free solvent systems. The reactions occurred in the temperature range of 60-100 oC with low catalyst loadings (0.15 5.00 wt %). Finally, a new compound, diisobornyl ether, was obtained through a novel onepot catalytic synthesis directly from camphene in the presence of dissolved or silicasupportedPW catalyst. The reaction occurred under near ambient conditions and diisobornyl ether was obtained with 90% selectivity at 50-60% camphene conversion, along with isoborneol. The novel ether was isolated as a mixture of meso and dl stereoisomers and fully characterized by MS-GC, NMR and IR spectroscopy. In all systems studied, PW has showed higher selectivity and catalytic activity than conventional acid catalysts such as H2SO4 and Amberlyst-15. The PW/SiO2 catalyst is stable to leaching in apolar solvents under the reaction conditions used and can be easily recovered and reused without the loss of activity and selectivity.